CTA513 : Digital animation technology / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course introduces students to the concept of 3D computer animation. Through practice and analysis, students will develop an understanding of the essential principles of 3D animation which include perspective, transformations, geometric and Spline-based modeling, lighting, camera work, rendering, basic inverse kinematics and modeling natural phenomena and motion through hands-on experience by utilizing computer tools and application. Concurrently, this course works alongside with the principles of animation.